Differential effects of low and high temperature stress on pollen germination and tube length of hazelnut (Corylus avellana L.) genotypes - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (ELSEVIER SCIENCE BV, 2019)
The pollen tube responses of four hazelnut genotypes to low (4 degrees C) and high (30 degrees C) temperature stress were determined. Pollen tubes stressed by 4 degrees C and 30 degrees C showed a reduction in both germination rate and tube length when compared to control (20 degrees C). Tolerance levels of genotypes were determined according to CSRI based on pollen germination rate and tube length. The genotypes Palaz, Yomra were determined as intermediate and, San, Kara as sensitive at 4 degrees C, while Palaz was determined as intermediate and, San, Kara, and Yomra were sensitive at 30 degrees C. To further distinguish between the genotypes, variation of some pollen tube characters such as tube abnormalities, callose localization and actin organization were examined. In addition, changes of superoxide dismutase, catalase activity and malondialdehyde content, used as stress indicators, were investigated. For each treatment, maximum tube abnormality occurred in Kara and the least abnormality rate was detected in Yomra. Dense callose accumulation was noticed near or at the apex in Kara for each temperature treatment, while callose accumulation was not found on the tube tips of other genotypes. Low and high-temperature treatment affected actin organization, especially in Kara. Maximum changes in superoxide dismutase, catalase activity and malondialdehyde content were observed for Kara, while the minimums were detected in Yomra at low and high temperature. Consequently, Kara and Yomra were determined as the most sensitive and most resistant geno-types, respectively.
Keywords: Genotype; Hazelnut; Pollen germination; Pollen tube growth; Temperature stress; CHICKPEA CICER-ARIETINUM; SELF-INCOMPATIBILITY; ACTIN-FILAMENTS; OXIDATIVE STRESS; COTTON CULTIVARS; SUCROSE SYNTHASE; NITRIC-OXIDE; CALCIUM-ION; CELL-GROWTH; CYTOSKELETON